2012
DOI: 10.1186/1746-6148-8-16
|View full text |Cite
|
Sign up to set email alerts
|

Global gene expression profiles of canine macrophages and canine mammary cancer cells grown as a co-culture in vitro

Abstract: BackgroundSolid tumours comprise various cells, including cancer cells, resident stromal cells, migratory haemopoietic cells and other. These cells regulate tumour growth and metastasis. Macrophages constitute probably the most important element of all interactions within the tumour microenvironment. However, the molecular mechanism, that guides tumour environment, still remains unknown. Exploring the underlying molecular mechanisms that orchestrate these phenomena has been the aim of our study.A co-culture of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
45
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 49 publications
(53 reference statements)
11
45
0
2
Order By: Relevance
“…Similarly to human breast cancer, in canine mammary cancer the macrophages also polarize toward the M2 phenotype [57]. Recently, we and others demonstrated that TAM infiltration is significantly associated with VEGF expression in malignant canine mammary tumors and that genes involved in angiogenic cellular pathways have been significantly upregulated in macrophages cocultured with canine mammary tumor cell lines [20, 58]. …”
Section: Inflammatory Cells and Sustained Angiogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly to human breast cancer, in canine mammary cancer the macrophages also polarize toward the M2 phenotype [57]. Recently, we and others demonstrated that TAM infiltration is significantly associated with VEGF expression in malignant canine mammary tumors and that genes involved in angiogenic cellular pathways have been significantly upregulated in macrophages cocultured with canine mammary tumor cell lines [20, 58]. …”
Section: Inflammatory Cells and Sustained Angiogenesismentioning
confidence: 99%
“…There are few studies in canine mammary cancer regarding the influence of immune cells in tumor invasion and metastasis [55, 64, 95]. The role of lymphocytes and macrophages in canine mammary tumor metastasis is not fully understood.…”
Section: Inflammatory Cells Tissue Invasion and Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal annealing time was 5 sec, whereas optimal temperature was 61°C. rps19 and hprt genes were used as a non-regulated reference for the normalization of target gene expression (sequences and reaction conditions has been previously given an account of: [23-25,28,29]. …”
Section: Methodsmentioning
confidence: 99%
“…Activation of CSF-1R by its ligand is likely to occur in an autocrine manner in tumor cells in which CSF-1R and CSF-1 are co-expressed, or in paracrine manner, when CSF-1R is stimulated by CSF-1 released by fibroblasts [6]. However, our recent studies have shown that CSF-1R in cancer cells can be stimulated by colony stimulating factor secreted by tumor-associated macrophages [8]. Interestingly, we showed that their co-culture leads to up-regulation of CSF in macrophages and up-regulation of CSFs and CSF-1R in cancer cells.…”
Section: Introductionmentioning
confidence: 99%